Field-induced slow-magnetic relaxation behaviours of Dy(III) ions in Dy2 dimeric complexes - Ahmed, Naushad; Nabi, Rizwan; Zhang, Xiaoguang; Darensbourg, Donald J. (Polyhedron, 2026)
A series of dimeric Dy2 complexes 1–3 was constructed using the 2,6-diacetylpyridine bis-salicyl hydrazone ligand system LN3O2 (provides equatorial N3O2 donor atoms) and linkers derived from hydrazine and vanillin (L1) or 4-hydroxybenzaldehyde (L2). These linkers coordinate from one of the axial sites of Dy(III) ions, and the other axial sites can be occupied by water or triphenylphosphine oxide (TPPO). Single crystal X-ray diffraction data revealed the molecular formulae of [Dy2 (H2LN3O2)2(L1)(H2O)2], [Dy2(H2LN3O2)2(L1)(TPPO)2], [Dy2(H2LN3O2)2(L2)(PPh3O)2], respectively, for complexes 1–3. The field-induced slow-magnetic relaxation behavior was observed for all these complexes 1–3, with Orbach Ueff = 11 cm−1 (τ0= 2.0 × 10−5 s−1), Ueff = 12.5 cm−1 (τ0= 7.9 × 10−6 s−1), and Ueff = 7.65 cm−1 (τ0= 9 × 10−5 s−1), respectively, having dominating Raman magnetic relaxation processes. Ab initio theoretical studies were performed on the optimized X-ray structures of these complexes to rationalize the experimental observations. Graphical abstract Herein, we report the synthesis, crystal structure, and magnetic properties of a series of Dy2 dimeric complexes 1–3. In these dimeric complexes, Dy(III) ions are coordinated by equatorial N3O2 donor atoms furnished by the doubly deprotonated hydrazone H2LN3O2 ligand systems, and the axial sites are either occupied by water or triphenylphosphine oxide. The two Dy(III) ions then connected with doubly deprotonated linkers L1 and L2. The role of linkers is to separate two Dy(III) ions with a suitable distance to avoid intramolecular dipolar interaction. We did not observe zero-field out-of-phase (χM”) signals in ac magnetic susceptibility measurements for any of these complexes 1–3, but on application of an optimum dc magnetic field, signals appeared. The data fitting and analysis revealed that Raman magnetic relaxations are active in all these reported complexes and are responsible for the low effective energy barrier Ueff for spin reversal through the Orbach process. Further, ab initio energy barrier, magnetic anisotropies, and plausible magnetic relaxation mechanism were computed using OpenMolcas. To understand the major types of intermolecular interactions and their effect on the magnetic relaxation, we also computed the Hirshfeld surface analysis using CrystalExplorer software. [Display omitted]